Sociodemographic and clinical-pathological profile of women hospitalized with metastatic or advanced local breast cancer - Eunice de Oliveira Lacerda Lima; Marcelle Miranda da Silva (Universidade Federal de Santa Maria, 2020)
Objective: to characterize the sociodemographic and clinical-pathological profile of women hospitalized with metastatic or advanced local breast cancer. Method: quantitative descriptive study, carried out in a hospital in Rio de Janeiro, Brazil, from March to July 2017. The study included 199 women hospitalized in the clinical ward. Data were collected from the medical records and through interviews, using a form that contained the variables of the profiles. The analysis was conducted using the Statistical Package for the Social Sciences, version 24. Results: 153 (76.88%) women were from 40 to 69 years old; 80 (40.20%) had incomplete elementary education; 181 (90.95%) lived with up to two minimum wages; 107 (53.77%) were diagnosed with stage III cancer; 145 (72.86%) were already in stage IV. 73 (36.68%) had the worst performance status, followed by 70 (35.18%) with performance status 3. Conclusion: the profile has shown delayed diagnoses and high levels of dependency, mostly in women with low educational levels and low socioeconomic conditions.